2020
DOI: 10.3390/membranes10100272
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Diffusion of H+, Li+, Na+, Cs+ Ions in Cation-Exchange Membranes Based on Polyethylene- and Sulfonated-Grafted Polystyrene Studied by NMR Technique and Ionic Conductivity Measurements

Abstract: The main particularities of sulfonate groups hydration, water molecule, and alkaline metal cation translation mobility were revealed by nuclear magnetic resonance (NMR) and ionic conductivity measurements techniques in cation-exchange membranes MSC based on cross-linked sulfonated polystyrene (PS) grafted on polyethylene with ion-exchange capacity of 2.5 mg-eq/g. Alkaline metal cation hydration numbers (h) calculated from temperature dependences of 1H chemical shift of water molecule for membranes equilibrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(65 citation statements)
references
References 35 publications
2
63
0
Order By: Relevance
“…Among them, the most stable are H 5 O 2 + and H 9 O 4 + ions, which are formed stepwise during membrane hydration. Their formation is confirmed by 1 H NMR data [ 72 , 107 , 108 , 109 , 110 ]. The authors of [ 111 ] reported a significant change in the properties of Nafion membranes with an increase in their hydration degree to above three water molecules per functional group.…”
Section: Ion Transfer In H + -Forms Of Membranementioning
confidence: 74%
See 4 more Smart Citations
“…Among them, the most stable are H 5 O 2 + and H 9 O 4 + ions, which are formed stepwise during membrane hydration. Their formation is confirmed by 1 H NMR data [ 72 , 107 , 108 , 109 , 110 ]. The authors of [ 111 ] reported a significant change in the properties of Nafion membranes with an increase in their hydration degree to above three water molecules per functional group.…”
Section: Ion Transfer In H + -Forms Of Membranementioning
confidence: 74%
“…The correctness of these conclusions is proved by the fact that the diffusion coefficients for aqueous solutions of alkali metal chlorides, determined using both methods, are equal and close to the values found by NMR for membranes samples [ 107 ]. It should also be mentioned that the type of ion-exchange membrane significantly affects the ratio of the diffusion coefficients measured using NMR spectroscopy and conductivity [ 133 ].…”
Section: Ion Transfer In H + -Forms Of Membranementioning
confidence: 89%
See 3 more Smart Citations